On track or not? Projecting the global multidimensional poverty index - Alkire, S; Nogales, R; Quinn, NN; Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2020)
In this paper we compute projections of global multidimensional poverty. We use recently published estimates of changes over time in multidimensional poverty for 75 countries, which are based on time-consistent indicators. We consider and evaluate different approaches to model the trajectories of countries’ achieved and future poverty reduction. Our preferred model respects theoretical bounds, is supported by empirical evidence, and ensures consistency of our main measure with its sub-indices. We apply this approach to examine whether countries will halve their poverty between 2015 and 2030 if observed trends continue. Our results suggest that if observed trends continue, 47 countries will have halved their poverty by 2030—irrespective of the underlying model. As the current COVID-19 pandemic may severely disrupt progress in poverty reduction, we also assess its potential impact using simulation techniques and evaluate the resulting setback. Our analyses suggest a setback to multidimensional poverty reduction of about 3–10 years.